2005
DOI: 10.1210/jc.2004-1496
|View full text |Cite
|
Sign up to set email alerts
|

Human Bladder as a Novel Target for Vitamin D Receptor Ligands

Abstract: Human prostate is now considered a target for vitamin D receptor (VDR) ligands, such as BXL-628. Because BXL-628 inhibited prostate growth without interfering with androgen signaling, it represents a new option for benign prostate hyperplasia (BPH) therapy. However, BPH symptoms are related not only to prostate size, but also to compensatory bladder hypertrophy and eventual overactivity. We now report that human bladder expresses VDR (determined by real-time PCR immunohistochemistry and Western blot) and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 49 publications
5
96
0
2
Order By: Relevance
“…Treatment of EAP by a VDR agonist represents a novel application for these hormone-like agents. The VDR is not only expressed by cells from classic target tissues as bone, bowel, and kidney but also in several others, including those derived from the urogenital sinus, such as prostate (49) and bladder (50). Interestingly, epithelial prostate cells express 1␣-hydroxylase, which is required for 1,25-dihydroxyvitamin D 3 synthesis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of EAP by a VDR agonist represents a novel application for these hormone-like agents. The VDR is not only expressed by cells from classic target tissues as bone, bowel, and kidney but also in several others, including those derived from the urogenital sinus, such as prostate (49) and bladder (50). Interestingly, epithelial prostate cells express 1␣-hydroxylase, which is required for 1,25-dihydroxyvitamin D 3 synthesis (51).…”
Section: Discussionmentioning
confidence: 99%
“…67 Bladder smooth muscle cells are known to express vitamin D receptors. 68 Morelli et al 69 studied the effects of BXL-628, a calcitriol analog shown to decrease prostate growth in preclinical and clinical studies, on Rho-kinase signaling in rat and human bladder. They found that carbachol responsiveness was delayed and Rho-kinase activity reduced by BXL-628 treatment because of impaired RhoA membrane translocation and activation.…”
Section: Effects On the Bladdermentioning
confidence: 99%
“…These receptors form an adaptive homeostatic network that bind lipophilic molecules, such as steroidal-based hormones, dietary factors, fatty acids and xenobiotics, with differing affinities to exert regulatory control over a wide range of gene targets (1)(2)(3). This network is integrated at multiple levels including ligand promiscuity, as demonstrated by the vitamin D receptor (VDR) and other receptors (4,5), and mutlimerisation.…”
Section: Introductionmentioning
confidence: 99%